Perovskite thin film, perovskite solar cell, preparation method and application

By doping 2-bromo-3-thiophene carboxylic acid additives in perovskite films, the film-forming and crystallization process of perovskites is solved, and the preparation of high-quality films and the improvement of perovskite solar cell performance is achieved.

CN119562746APending Publication Date: 2025-03-04TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680626.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the large-area preparation process, the growth of perovskite grains is uncontrollable, resulting in poor film density, which in turn affects the performance of perovskite solar cells.

Method used

Doping 2-bromo-3-thiophene carboxylic acid additives in the perovskite films, delaying film formation crystallization through the carboxyl group and perovskite formation, improving film formation quality, and achieving body passivation through unsaturated sulfur in bromine atoms and thiophene.

Benefits of technology

Form a high-quality perovskite film, improve the performance of perovskite solar cells and achieve large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562746A_ABST
    Figure CN119562746A_ABST
Patent Text Reader

Abstract

The invention belongs to the photovoltaic field, and particularly relates to a perovskite thin film, a perovskite solar cell, a preparation method and application. The perovskite thin film provided by the invention comprises a perovskite structure substance and 2-bromo-3-thiophene carboxylic acid. The perovskite thin film doped with the 2-bromo-3-thiophene carboxylic acid additive is excellent in film forming quality, the perovskite solar cell using the perovskite thin film is excellent in performance, and production of the large-area perovskite solar cell is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaics, and in particular relates to a perovskite film, a perovskite solar cell, and a preparation method and use thereof. Background Art

[0002] In recent years, photovoltaic (PV) technology has stood out among various new energy technologies due to its high performance and low pollution. Furthermore, metal halide perovskite solar cells have attracted attention in the past decade due to their excellent device performance and low-cost manufacturing process. To date, the operating stability of perovskite solar cells has been significantly improved, and the highest power conversion efficiency (PCE) of small-area perovskite solar cells has reached 25.7%, which is close to the record efficiency of crystalline silicon (c-Si) solar cells. Perovskite solar cell technology is moving towards commercialization.

[0003] In commercially mature technologies, the device area has increased by an order of magnitude. 2 Battery, micromodule (19.32cm 2 ) and larger modules (756cm 2 ) are 23.7%, 21.4% and 18.2% respectively. It can be seen that as the device area increases by one order of magnitude, the efficiency of current perovskite solar cells decreases by an average of 2%-3% in absolute value, which is much higher than the general decrease. The main reason for this is that the growth of perovskite grains is uncontrollable during large-scale preparation, and the time window is short, resulting in uneven growth of perovskite grains, which in turn leads to pinholes in the perovskite film and poor density, which further leads to poor performance of perovskite solar cells.

[0004] At present, there are three main methods for regulating perovskite crystallization over a large area. The first is to adjust the ratio of perovskite solvents and increase the solvent with high DN value to achieve uniform growth of perovskite grains; the second is to adjust the growth of perovskite grains by adding halides or organic molecules to the perovskite precursor; the third is to improve the wettability of the substrate through interface modification, so as to achieve the growth of a more ideal perovskite film. However, all three methods have certain problems. Although solvent engineering can effectively regulate the growth of the film, it cannot achieve the effect of body passivation; the passivation and crystal growth effects of adding halides or organic molecules are poor; the interface modification method is more complicated and not conducive to industrialization.

[0005] Therefore, it is urgent to develop a perovskite film with bulk passivation effect, simple preparation process and excellent film quality, so as to improve the performance of perovskite solar cells and realize the production of large-area perovskite solar cells. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention dopes a 2-bromo-3-thiophene carboxylic acid additive in a perovskite film. The carboxyl group in the 2-bromo-3-thiophene carboxylic acid will form an intermediate with the perovskite, delaying film crystallization and improving film quality; the Br in the 2-bromo-3-thiophene carboxylic acid can improve the quality of the perovskite film, making the film more compact; the S in the thiophene in the 2-bromo-3-thiophene carboxylic acid is in an unsaturated state, and can coordinate with the uncoordinated Pb in the perovskite to achieve the effect of body passivation. In summary, doping the 2-bromo-3-thiophene carboxylic acid additive in the perovskite film can regulate the film crystallization process of the perovskite, forming a perovskite film with excellent film quality, thereby improving the performance of the perovskite solar cell and realizing the production of large-area perovskite solar cells.

[0007] Specifically, the present invention provides a perovskite film, which includes a perovskite structure material and 2-bromo-3-thiophenecarboxylic acid.

[0008] In one or more embodiments, the chemical formula of the perovskite structure material is ABX3, and the A ion is selected from the group consisting of methylamine ion, formamidine ion and Cs + One or more of the following, B ion is Pb 2+ and / or Sn 2+ , X ion is selected from I - Br - and Cl - One or more of .

[0009] In one or more embodiments, the molar ratio of the perovskite structure material to 2-bromo-3-thiophenecarboxylic acid is 1:(0.0038-0.0093).

[0010] In one or more embodiments, the perovskite film has a thickness of 450-650 nm.

[0011] The present invention provides a method for preparing the perovskite film of the present invention, the method comprising the following steps: uniformly dispersing a raw material of a perovskite structure material and 2-bromo-3-thiophenecarboxylic acid in a solvent to obtain a perovskite precursor solution, coating the perovskite precursor solution, annealing, and obtaining a perovskite film.

[0012] In one or more embodiments, the concentration of the perovskite structure substance in the perovskite precursor solution is 1-1.6 mol / L.

[0013] In one or more embodiments, the concentration of 2-bromo-3-thiophenecarboxylic acid in the perovskite precursor solution is 0.8-1.2 mg / L.

[0014] In one or more embodiments, in the perovskite precursor solution, the solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone and N-methylpyrrolidone.

[0015] In one or more embodiments, the coating method is spin coating, slot coating, knife coating, or spray coating.

[0016] In one or more embodiments, the annealing temperature is 100-150°C.

[0017] In one or more embodiments, the annealing time is 15-35 min.

[0018] The present invention provides a perovskite solar cell comprising the perovskite film of the present invention.

[0019] The present invention provides a use of the perovskite film of the present invention in preparing a solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the structure of a perovskite solar cell prepared according to some embodiments of the present invention, Figure 1 Here, ETL stands for electron transport layer, HTL stands for hole transport layer, and PVK stands for perovskite film.

[0021] Figure 2 This is a scanning electron microscope image (SEM) of the perovskite film containing 2-bromo-3-thiophenecarboxylic acid additive prepared in Example 1 of the present invention.

[0022] Figure 3 This is a scanning electron microscope image (SEM) of the perovskite film without 2-bromo-3-thiophenecarboxylic acid additive prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0024] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0025] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0027] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0028] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0030] The present invention provides a perovskite film including a perovskite structure material and 2-bromo-3-thiophene carboxylic acid. The present invention dopes a 2-bromo-3-thiophene carboxylic acid additive into the perovskite film, and the carboxyl group in the 2-bromo-3-thiophene carboxylic acid forms an intermediate with the perovskite, delays film crystallization, and improves film quality; Br in the 2-bromo-3-thiophene carboxylic acid can improve the quality of the perovskite film, making the film more compact; S in the thiophene in the 2-bromo-3-thiophene carboxylic acid is in an unsaturated state, and can coordinate with uncoordinated Pb in the perovskite to achieve the effect of body passivation. In summary, doping the perovskite film with a 2-bromo-3-thiophene carboxylic acid additive can regulate the film crystallization process of the perovskite, form a perovskite film with excellent film quality, and then improve the performance of the perovskite solar cell, and realize the production of large-area perovskite solar cells.

[0031] In the present invention, the chemical formula of the perovskite structure material can be ABX3, and A can be selected from methylamine ion (MA + ), formamidinium ion (FA + ) and Cs + One or more of, B can be Pb 2+ and / or Sn2+ , X can be selected from I - Br - and Cl - For example, the perovskite structure material is FAPbI3, FAMAPbI3, FACsPbI3 or FAMACsPbI3.

[0032] In the present invention, the molar ratio of the perovskite structure material to 2-bromo-3-thiophene carboxylic acid can be 1:(0.0038-0.0093), such as 1:0.0038, 1:0.0040, 1:0.0045, 1:0.0050, 1:0.0055, 1:0.0060, 1:0.0065, 1:0.0070, 1:0.0075, 1:0.0080, 1:0.0085, 1:0.0090. In the present invention, the molar ratio of the perovskite structure material to 2-bromo-3-thiophene carboxylic acid is controlled within the above range, which is conducive to improving the film quality of the perovskite film, thereby improving the filling factor and photoelectric conversion efficiency of the perovskite solar cell, and realizing the production of large-area perovskite solar cells.

[0033] In the present invention, the thickness of the perovskite film may be 450-650 nm, for example, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm.

[0034] The present invention provides a method for preparing the perovskite film of the present invention, which may include the following steps: uniformly dispersing raw materials of a perovskite structure material and 2-bromo-3-thiophenecarboxylic acid in a solvent to obtain a perovskite precursor solution, coating the perovskite precursor solution, and annealing to obtain a perovskite film.

[0035] In the perovskite precursor solution of the present invention, the concentration of the perovskite structure substance can be 1-1.6 mol / L, for example, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L.

[0036] In the perovskite precursor solution of the present invention, the concentration of 2-bromo-3-thiophene carboxylic acid can be 0.8-1.2 mg / L, for example 0.8 mg / L, 0.9 mg / L, 1.0 mg / L, 1.1 mg / L, 1.2 mg / L. In the present invention, controlling the concentration of 2-bromo-3-thiophene carboxylic acid within the above range is beneficial to improving the film quality of the perovskite film, thereby improving the filling factor and photoelectric conversion efficiency of the perovskite solar cell, and realizing the production of large-area perovskite solar cells.

[0037] In the present invention, in the perovskite layer precursor solution, the solvent may be one or more selected from N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), γ-butyrolactone (GBL) and N-methylpyrrolidone (NMF). In some embodiments, the organic solvent is selected from two of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone and N-methylpyrrolidone, and the volume ratio of the two organic solvents is (3-5):1. For example, the organic solvent may be a mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of (3-5):1, the organic solvent may also be a mixture of γ-butyrolactone and N-methylpyrrolidone in a volume ratio of (3-5):1, and the organic solvent may also be a mixture of N,N-dimethylformamide and N-methylpyrrolidone in a volume ratio of (3-5):1.

[0038] In the present invention, the coating method of the perovskite precursor solution can be spin coating, slit coating, blade coating or spray coating.

[0039] In the present invention, the annealing temperature for preparing the perovskite film can be 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C.

[0040] In the present invention, the annealing time for preparing the perovskite film can be 10-35 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min.

[0041] The present invention provides a perovskite solar cell comprising the perovskite film of the present invention.

[0042] In the present invention, the perovskite solar cell includes a single junction perovskite solar cell and a tandem perovskite solar cell. In the present invention, the perovskite solar cell includes a formal perovskite solar cell and an inverted perovskite solar cell. In the present invention, the perovskite solar cell may include a formal single junction perovskite solar cell, an inverted single junction perovskite solar cell, a formal tandem perovskite solar cell and an inverted tandem perovskite solar cell.

[0043] In the present invention, the formal single-junction perovskite solar cell may include a transparent conductive substrate, an electron transport layer, a perovskite film, a hole transport layer and a back electrode in sequence.

[0044] In the present invention, the inverted single-junction perovskite solar cell may include a transparent conductive substrate, a hole transport layer, a perovskite film, an electron transport layer and a back electrode in sequence.

[0045] In some embodiments, the electron transport layer and the back electrode of the inverted single-junction perovskite solar cell may further include a hole blocking layer.

[0046] In the present invention, the transparent conductive substrate may be one of fluorine-doped tin oxide (FTO) glass, indium tin oxide (ITO) glass or a flexible indium tin oxide (ITO) conductive substrate.

[0047] In the present invention, the hole transport layer can be one or more selected from metal oxides, single-molecule self-assembled materials containing phosphoric acid groups and single-molecule self-assembled materials containing carboxylic acid groups; the single-molecule self-assembled materials containing phosphoric acid groups can be one or more selected from [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz) and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz).

[0048] In the present invention, the electron transport layer can be selected from one or more of C60 or fullerene derivatives (PCBM), and the fullerene derivative can be [6,6]-phenyl-C61-butyric acid isomethyl ester (

[60] PCBM) or [6,6]-phenyl-C71-butyric acid isomethyl ester (

[70] PCBM).

[0049] In the present invention, the hole blocking layer may be 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) and / or SnO2.

[0050] In the present invention, the back electrode may be Ag, Cu or Au.

[0051] In the present invention, the thickness of the hole transport layer may be 2-5 nm, for example, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, or 5 nm.

[0052] In the present invention, the thickness of the electron transport layer can be 15-30 nm, for example, 15 nm, 17 nm, 20 nm, 22 nm, 24 nm, 26 nm, 28 nm, and 30 nm.

[0053] In the present invention, the thickness of the hole blocking layer may be 5-15 nm, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, and 15 nm.

[0054] In the present invention, the thickness of the back electrode may be 60-150 nm, for example, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, or 150 nm.

[0055] In the present invention, the method for preparing a formal single-junction perovskite solar cell may include:

[0056] (1) depositing an electron transport layer on the surface of a transparent conductive substrate;

[0057] (2) depositing a perovskite film on the surface of the electron transport layer;

[0058] (3) depositing a hole transport layer on the surface of the perovskite film;

[0059] (4) Depositing a back electrode on the surface of the hole transport layer to obtain a formal single-junction perovskite solar cell.

[0060] In the present invention, the method for preparing an inverted single-junction perovskite solar cell may include:

[0061] (1) depositing a hole transport layer on the surface of a transparent conductive substrate;

[0062] (2) depositing a perovskite film on the surface of the hole transport layer;

[0063] (3) depositing an electron transport layer on the surface of the perovskite film;

[0064] (4) A back electrode is deposited on the surface of the electron transport layer to obtain an inverted single-junction perovskite solar cell.

[0065] In the present invention, the method for preparing the hole transport layer may include: coating a hole transport layer precursor solution on a transparent conductive substrate, and then annealing to obtain the hole transport layer.

[0066] In the present invention, the coating method of the hole transport layer precursor solution can be spin coating, slit coating, blade coating or spray coating.

[0067] In the present invention, the solvent in the hole transport layer precursor solution may be ethanol and / or isopropanol.

[0068] In the present invention, the annealing temperature for preparing the hole transport layer can be 100-120°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C.

[0069] In the present invention, the annealing time for preparing the hole transport layer can be 10-15 min, for example, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min.

[0070] The method for preparing an inverted single-junction perovskite solar cell of the present invention may further include: depositing a hole blocking layer on the surface of the electron transport layer.

[0071] In some embodiments, a method of preparing an inverted single junction perovskite solar cell comprises:

[0072] (1) depositing a hole transport layer on the surface of a transparent conductive substrate;

[0073] (2) depositing a perovskite film on the surface of the hole transport layer;

[0074] (3) depositing an electron transport layer on the surface of the perovskite film;

[0075] (4) depositing a hole blocking layer on the surface of the electron transport layer;

[0076] (4) A back electrode is deposited on the surface of the hole blocking layer to obtain an inverted single-junction perovskite solar cell.

[0077] Compared with the prior art, the present invention has the following beneficial effects:

[0078] (1) The present invention achieves the regulation of perovskite film crystal growth by adding 2-bromo-3-thiophenecarboxylic acid to the perovskite precursor solution, thereby achieving the preparation of high-quality films;

[0079] (2) The present invention can achieve the effect of defect passivation while regulating the growth of perovskite grains;

[0080] (3) The material cost of the present invention is relatively low, which is conducive to commercialization;

[0081] (4) The preparation process of the present invention is simple and has obvious effects.

[0082] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0083] Example 1

[0084] In this embodiment, a perovskite film containing 2-bromo-3-thiophenecarboxylic acid is prepared, and the specific steps are as follows:

[0085] (1) Cleaning FTO conductive glass (fluorine-doped SnO2 conductive glass): Place the FTO conductive glass in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water, isopropanol, and ethanol in sequence. Each cleaning step takes 30 minutes. After cleaning, blow dry with a N2 air gun for later use. Perform P1 laser etching, and finally treat with UV-zone for 30 minutes to obtain clean FTO conductive glass (transparent conductive substrate).

[0086] (2) Preparation of hole transport layer: 120 mg Me-4PACz was dissolved in 20 mL ethanol and stirred for 3 h to obtain a hole transport layer precursor solution. The hole transport layer precursor solution was slit coated on a clean FTO conductive glass at a coating speed of 30 mm / s and a gap value of 100 μm. After coating, annealing was performed at a temperature of 100 °C and an annealing time of 10 min to obtain a hole transport layer with a thickness of 3 nm.

[0087] (3) Preparation of perovskite film: Cs 0.15 FA 0.85 PbI3 powder was dissolved in a mixed solvent (DMF and DMSO in a volume ratio of 4:1), and then 2-bromo-3-thiophenecarboxylic acid was added and stirred at 25°C until all dissolved to obtain a volume of 25 mL, a 2-bromo-3-thiophenecarboxylic acid concentration of 1 mg / mL, and Cs 0.15 FA 0.85 The perovskite precursor solution has a PbI3 concentration of 1 mmol / mL; the perovskite precursor solution is coated on the hole transport layer at a coating speed of 30 mm / s and a gap value of 100 μm. After coating, annealing treatment is performed at an annealing temperature of 130°C and an annealing time of 30 minutes to obtain a perovskite film with a thickness of 550 nm.

[0088] Comparative Example 1

[0089] The only difference between this comparative example and Example 1 is that the perovskite precursor solution of this comparative example does not contain 2-bromo-3-thiophenecarboxylic acid.

[0090] Test Example 1

[0091] The perovskite films prepared in Example 1 and Comparative Example 1 were tested by scanning electron microscope, and the results were as follows: Figure 2 and Figure 3 .Depend on Figure 2 It can be seen that the perovskite film containing 2-bromo-3-thiophenecarboxylic acid additive has fewer holes, good density and higher film quality; Figure 3 It can be seen that the perovskite film without 2-bromo-3-thiophenecarboxylic acid additive has more holes and the film quality is poor.

[0092] Example 2

[0093] In this embodiment, the structure is prepared as Figure 1 The perovskite solar cell shown in the figure has the following specific steps:

[0094] (1) Cleaning FTO conductive glass (fluorine-doped SnO2 conductive glass): Place the FTO conductive glass in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water, isopropanol, and ethanol in sequence. Each cleaning step takes 30 minutes. After cleaning, blow dry with a N2 air gun for later use. Perform P1 laser etching, and finally treat with UV-zone for 30 minutes to obtain clean FTO conductive glass (transparent conductive substrate).

[0095] (2) Preparation of hole transport layer: 120 mg Me-4PACz was dissolved in 20 mL ethanol and stirred for 3 h to obtain a hole transport layer precursor solution. The hole transport layer precursor solution was slit coated on a clean FTO conductive glass at a coating speed of 30 mm / s and a gap value of 100 μm. After coating, annealing was performed at a temperature of 100 °C and an annealing time of 10 min to obtain a hole transport layer with a thickness of 3 nm.

[0096] (3) Preparation of perovskite film: Cs 0.15 FA 0.85 PbI3 powder was dissolved in a mixed solvent (DMF and DMSO in a volume ratio of 4:1), and then 2-bromo-3-thiophenecarboxylic acid was added and stirred at 25°C until all dissolved to obtain a volume of 25 mL, a 2-bromo-3-thiophenecarboxylic acid concentration of 1 mg / mL, and Cs 0.15 FA 0.85 The perovskite precursor solution has a PbI3 concentration of 1 mmol / mL; the perovskite precursor solution is coated on the hole transport layer at a coating speed of 30 mm / s and a gap value of 100 μm. After coating, annealing is performed at a temperature of 130°C and an annealing time of 30 min to obtain a perovskite film with a thickness of 550 nm;

[0097] (4) Preparation of electron transport layer: on the perovskite film Vapor depositing C60 to obtain an electron transport layer with a thickness of 30 nm;

[0098] (5) Preparation of hole blocking layer: on the electron transport layer BCP was evaporated to obtain a hole blocking layer with a thickness of 6 nm, followed by P2 laser etching;

[0099] (6) Preparation of back electrode: Copper is thermally evaporated on the surface of the hole blocking layer to obtain a back electrode with a thickness of 100 nm, and then P3 and P4 laser etching are performed to obtain a perovskite solar cell.

[0100] Example 3

[0101] The only difference between this embodiment and embodiment 2 is that the concentration of the perovskite precursor solution 2-bromo-3-thiophenecarboxylic acid in this embodiment is 0.8 mg / mL.

[0102] Example 4

[0103] The only difference between this embodiment and embodiment 2 is that the concentration of the perovskite precursor solution 2-bromo-3-thiophenecarboxylic acid in this embodiment is 1.2 mg / mL.

[0104] Comparative Example 2

[0105] The only difference between this comparative example and Example 2 is that the perovskite precursor solution of this comparative example does not contain 2-bromo-3-thiophenecarboxylic acid.

[0106] Comparative Example 3

[0107] The only difference between this comparative example and Example 2 is that the concentration of the perovskite precursor solution 2-bromo-3-thiophenecarboxylic acid in this comparative example is 0.5 mg / mL.

[0108] Comparative Example 4

[0109] The only difference between this comparative example and Example 2 is that the concentration of the perovskite precursor solution 2-bromo-3-thiophenecarboxylic acid in this comparative example is 1.5 mg / mL.

[0110] Comparative Example 5

[0111] The only difference between this comparative example and Example 2 is that the additive of the perovskite precursor solution in this comparative example is replaced by 2-fluoro-3-thiophenecarboxylic acid instead of 2-bromo-3-thiophenecarboxylic acid.

[0112] Test Example 2

[0113] Performance test of perovskite solar device: Under 25°C and AM 1.5G standard solar spectrum, using a solar simulator, the voltage range was set to 2V to -0.5V, the current output of the inverted perovskite solar cells prepared in Examples 2-4 and Comparative Examples 2-5 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell effective area was 49cm 2 , the number of subcells is 10, and the incident light power (Pin) is 100mW / cm 2 The open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 2-4 and Comparative Examples 2-5 were obtained according to the characteristic curves.

[0114] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.

[0115] (2) Short-circuit current (Isc): The current value when the voltage is zero is the short-circuit current (Isc).

[0116] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.

[0117] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.

[0118] The test results of the open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 2-4 and Comparative Examples 2-5 are shown in Table 1.

[0119] Table 1: Open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency of perovskite solar cells prepared in Examples 2-4 and Comparative Examples 2-5

[0120] <![CDATA[V OC (V)]]> <![CDATA[I SC (A)]]> FF(%) PCE(%) Example 2 11.02 0.111 72.16 17.97 Example 3 10.10 0.11 77.86 17.69 Example 4 11.05 0.11 69.75 17.34 Comparative Example 2 10.98 0.112 63.33 15.89 Comparative Example 3 11.10 0.109 67.75 16.77 Comparative Example 4 10.97 0.109 67.24 16.44 Comparative Example 5 10.12 0.111 70.88 16.2

Claims

1. A perovskite film, characterized in that: The perovskite film includes a perovskite structural material and 2-bromo-3-thiophenecarboxylic acid.

2. The perovskite film according to claim 1, characterized in that The chemical formula of the perovskite structure material is ABX3, and the A ion is selected from methylamine ion, formamidine ion and Cs + One or more of the following, B ion is Pb 2+ and / or Sn 2+ , X ion is selected from I - Br - and Cl - One or more of .

3. The perovskite film according to claim 1, characterized in that The molar ratio of the perovskite structure material to 2-bromo-3-thiophenecarboxylic acid is 1:(0.0038-0.0093).

4. The perovskite film according to claim 1, characterized in that The thickness of the perovskite film is 450-650nm.

5. A method for preparing the perovskite film according to claim 1, characterized in that: The method comprises the following steps: uniformly dispersing raw materials of perovskite structure material and 2-bromo-3-thiophene carboxylic acid in a solvent to obtain a perovskite precursor solution, coating the perovskite precursor solution, annealing, and obtaining a perovskite film.

6. The method according to claim 5, characterized in that The method has one or more of the following features: In the perovskite precursor solution, the concentration of the perovskite structure substance is 1-1.6 mol / L; In the perovskite precursor solution, the concentration of 2-bromo-3-thiophenecarboxylic acid is 0.8-1.2 mg / L; In the perovskite precursor solution, the solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone and N-methylpyrrolidone.

7. The method according to claim 5, characterized in that The coating methods are spin coating, slot coating, doctor blade coating or spray coating.

8. The method according to claim 5, characterized in that Annealing temperature is 100-150°C; and / or The annealing time is 15-35min.

9. A perovskite solar cell comprising the perovskite thin film according to any one of claims 1 to 4.

10. Use of the perovskite film according to any one of claims 1 to 4 in preparing solar cells.